PENAMBAHAN EKSTRAK DAUN KEMANGI DAN LAMA PERENDAMAN TERHADAP MUTU DAN DAYA AWET IKAN NILA (Oreachromis niloticus) SEGAR - Enjel Souhoka; Alwi Smith; Ine Airini (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: Nila is a tropical fish that likes shallow water. Nila has better nutritional content compared to other freshwater fish, but Nila is also a food that is quickly damaged and spoiled. Pharmacological testing shows that basil has antibacterial activity. Basil leaves contain saponins, flavonoids and tannins which have many benefits besides being a spice in cooking it is also beneficial for bodily health. Method: This study immersed Nila in basil leaf extract (30 ml, 60 ml, 90 ml) dissolved in water to a volume of 0.5 liters for 30 minutes. After that it is stored at room temperature for 0 hours, 4 hours and 6 hours. Results: The results of the study using the ANOVA test showed that with the addition of basil leaf extract T1 (30ml), T2 (60 ml) and T3 (90 ml) there was no change in texture, color, odor and eyes on the 4 hour immersion while in the 6 hour immersion there was a change in texture and color. Conclusion: Based on the results and discussion above, it can be concluded that the addition of basil leaf extract to the freshness of Nila can be seen in 4 hours of immersion because, the results obtained are good, there is no change in the texture, color, odor and eye categories based on 4 sensory test scales. This happens because there is no enzyme, microorganism and chemical activity so that the freshness of the fish is maintained.